The Influence of Lecturers' Digital Leadership to Digital Competence of Students at Kurnia Jaya Persada University - Ayuandira, Ririn; Irmawati, Irmawati; Ramadan, Farhan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
Study entitled The Influence of Lecturers' Digital Leadership to Digital Competence of Students at Kurnia Jaya Persada University This aim for analyze implementation digital leadership in context education tall as well as test its influence to student digital competency in face global competition. Focus study directed at perception student to characteristics digital leadership and challenges leadership education in the era of transformation technology. Research use approach quantitative with design descriptive and explanatory. Population study is student from five study programs with amount sample A total of 78 respondents were determined through method census. Data collection was carried out use questionnaire structured. Data analysis was carried out using SPSS version 26 through regression testing for identify strength relationships and contributions influence intervariable. Research result show that Digital Leadership lecturer influential strong and significant to Student Digital Competence with The R value is 0.805 and the R Square is 0.649. The findings This indicates that 64.9% of the variation student digital competency can explained by practice digital leadership of lecturers, which places Digital Leadership as determinant main in form students' digital readiness.